The role of Muslim identity on perceived workplace religious discrimination of Muslim women working in Kwa-Zulu Natal - Ponnadu, Coral J (Organisational Psychology, 2023)
The South African Constitution provides a comprehensive list of rights, many of which are important, directly or indirectly, to meet the needs of religious minorities in the country. However, due to South Africa being a secular state and also having particular needs, many workplaces tend to adopt this approach which leads to a conflict between Muslims' religious obligations and the rules of the workplace. As a result, Muslim employees may perceive that their employers are religiously discriminating against them. Muslim women may face more discrimination than Muslim men as their stigma is less concealable due to their modest dressing and the hijab (religious identity marker). Surprisingly, there has been an increase in cases of religious discrimination against Muslim women. To elucidate, these Muslim women employees were asked to remove their hijab on their job as it somewhat violated the company policies. Therefore, presenting a challenge for Muslim women as their religious identity is part of their self-concept and they are required to follow their religious obligations. Informed by theories such as Social Identity Theory and Intergroup Threat Theory, the present study utilised a cross-sectional design to examine the role of Muslim identity in perceived religious discrimination in the workplace. To gain insight about the hijab in various contexts, the current study also examined the comfortability of wearing the hijab in different contexts. The participants were 75 Muslim women living and working in organisations in KwaZulu-Natal, South Africa. The findings of this research indicate that the dimensions of Muslim identity are not significant predictors of perceived religious discrimination; however, psychological identity can lead Muslim women to perceive less or no discrimination. Furthermore, the ANOVA showed that Muslim women did not feel significantly more comfortable wearing the hijab in certain contexts. This study offered implications for both research and practice and made significant recommendations for future research.